A Review on Bismuth Oxyhalide (BiOX, X=Cl, Br, I) Based Photocatalysts for Wastewater Remediation - Lv, Xincong; Lam, Frank Leung Yuk; Hu, Xijun (Frontiers in Catalysis, 2022)
Solar energy transformation over semiconductor-based photocatalysis is ideal for solving environment issues and the development of sustainable future. Recently, the layered bismuth oxyhalides (BiOX, X = F, Cl, Br and I) attracts wide attention due to the potential photocatalysts for energy and environment applications. This review provides a summary of recent development on the design of BiOX composites to improve the energy conversion efficiency. Particular focus is paid to the emerging techniques for the enhancement of the photocatalytic behavior of BiOX, such as heterojunction engineer, metal/non-metal doping, interfacing with carbon and coupling with noble metal. The application of BiOX-based composites in wastewater remediation are also reviewed in terms of organics photocatalytic oxidation and heavy metal ion photocatalytic reduction. Finally, the future challenges and opportunities of BiOX-based photocatalysts for practical application are discussed. Overall, this review provides a good basis for the innovative design of BiOX-based materials for environmental and especially energy-based applications.